ON LESSONS OF ONE EXPERIMENT - M. G. Aliev (Юг России: экология, развитие)
Aim. The paper presents the analysis of the political and socio-economic situation in the Republic of Dagestan, North-Caucasian Federal District of the Russian Federation for the period from 2006 to 2010.Discussion. We discuss the interrelation of the political situation and socio - economic stability at the national level. We also identified the basic problems of socio-economic and political stability in relation to the Republic of Dagestan; mechanisms to ensure the socio-economic recovery, political modernization, the creation of modern political institutions, formation of civil society and the rule of law to ensure the rights and freedoms of the individual. We discussed the questions of efficiency of public administration in the territory of Dagestan, economic leverage to market relations in order to reduce the dependence of the national budget on subsidies; administrative reform to reduce administrative barriers to minimize undue interference by public authorities in the activities of economic entities.Conclusion. It was indicated that the goal of economic modernization has been the elimination of socio-economic backwardness of Dagestan from other regions of Russia, changing the structure of the economy, the revival of the industry based on new technology, enhancing its competitiveness, ensuring the normal functioning of market institutions, the creation of modern jobs. To do this, we have changed approaches to taxation, fiscal - financial, scientific and technical policy in the region, the work of local governments.